The risk factors and preventive measures for the recurrence of endometrial polyps - Doobaly, Nitisha; Wang, Xiuli; Lin, Minjuan; Zhu, Shu; Wang, Xia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Endometrial polyps (EPs) are a frequently encountered gynecologic disease with abnormal uterine bleeding and infertility being the two common presenting problems, and hysteroscopic polypectomy is an effective method to remove them. The postoperative polyp recurrence might result in reappearance of abnormal uterine bleeding or infertility, whereas factors influencing the postoperative recurrence potential have limited data. Endometrial polyp recurrence remains a concern with recurrence rates of 2.5% to 43.6%. As such, it is critical to identify the risk factors and the preventive measures for endometrial recurrence, especially in reproductive-age women desiring future conception, to aid in clinical counselling and decision making. The recurrence of EPs is related to estrogen stimulation and endometrial hyperplasia. The progesterone-containing drugs are currently the most commonly used method to prevent the recurrence of EPs. In this article, authors aim to discuss the high-risk factors of EPs recurrence and the preventive measures for EPs recurrence. The preventive measures will focus on the combined oral contraceptives (COCs) and the levonorgestrel-releasing intrauterine system (LNG-IUS).